A new, one-pot, multicomponent synthesis of 5-aza-9-deaza-adenines under microwave irradiation - Lim, Felicia Phei Lin; Luna, Giuseppe; Dolzhenko, Anton (Pergamon, 2014)
A new, practical, three-component method for the synthesis of 5-aza-9-deaza-adenines is developed. Aminopyrazoles react in a one-pot fashion with triethyl orthoformate and cyanamide under microwave irradiation affording 5-aza-9-deaza-adenines in good yields and high purity. The main advantages of this method are the operational simplicity, accessibility and high efficiency